2019
DOI: 10.1175/jamc-d-18-0177.1
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Cold-Season Short-Wave Troughs in the Great Lakes Region and Their Concurrence with Lake-Effect Clouds

Abstract: The downwind shores of the Laurentian Great Lakes region often receive prolific amounts of lake-effect snowfall during the cold season (October–March). The location and intensity of this snowfall can be influenced by upper-tropospheric features such as short-wave troughs. A 7-yr cold-season climatology of 500-hPa short-wave troughs was developed for the Great Lakes region. A total of 607 short-wave troughs were identified, with an average of approximately 87 short waves per cold season. Five classes of short-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Upper atmospheric disturbances and clippers were the second most frequent storms, both occurring 233 times during the study period. Both of these storm types are often associated with the conditions necessary for the formation of lake‐effect snow including the advection of cold air over the Great Lakes, west‐northwest winds over Central New York, and a substantial fetch across Lake Ontario (Thomas and Martin, 2007; Metz et al ., 2019). Therefore, clippers and upper atmospheric disturbances may often prelude lake‐effect snowstorms.…”
Section: Discussionmentioning
confidence: 99%
“…Upper atmospheric disturbances and clippers were the second most frequent storms, both occurring 233 times during the study period. Both of these storm types are often associated with the conditions necessary for the formation of lake‐effect snow including the advection of cold air over the Great Lakes, west‐northwest winds over Central New York, and a substantial fetch across Lake Ontario (Thomas and Martin, 2007; Metz et al ., 2019). Therefore, clippers and upper atmospheric disturbances may often prelude lake‐effect snowstorms.…”
Section: Discussionmentioning
confidence: 99%
“…6c). These surface features occur within quasi-zonal flow at 500-hPa across North America with a short-wave trough (e.g., Metz et al 2019) over the Intermountain West and shortwave ridge over the Great Lakes Region (Fig. 6d).…”
Section: Results: Band Morphology and Classification A Elcp Morphologymentioning
confidence: 99%
“…As Wright et al (2013) suggest, frozen lakes and cooler lake surface temperatures will shrink the snow bands and confine them closer to the lake shore, which ultimately diminishes lake-effect contributions further from the lake. Furthermore, the location of snow bands is influenced by the presence of upper-tropospheric short-wave troughs (Metz et al, 2019). Metz et al (2019) found that lake-effect bands concurrent with short-wave troughs were most common during the peak season (December-January), which may displace snow bands directly east or northeast of the long-axis of the lake.…”
Section: Snowfall Contributions From Lake-effect Snowmentioning
confidence: 99%
“…Furthermore, the location of snow bands is influenced by the presence of upper-tropospheric short-wave troughs (Metz et al, 2019). Metz et al (2019) found that lake-effect bands concurrent with short-wave troughs were most common during the peak season (December-January), which may displace snow bands directly east or northeast of the long-axis of the lake.…”
Section: Snowfall Contributions From Lake-effect Snowmentioning
confidence: 99%